PERAN PROGRAM STUDI PENDIDIKAN SEJARAH DI ERA REVOLUSI INDUSTRI 4.0 - Eko Heri Widiastuti; Nuryanti Nuryanti; Zusrotin Zusrotin (BIHARI: JURNAL PENDIDIKAN SEJARAH DAN ILMU SEJARAH, 2021)
ABSTRACTHistory Education Study Program is not a favorite study program in a university, especially at this time in the era of the industrial revolution 4.0, an increasingly modern era with science and technology that continues to develop. Through historical learning, the young generation is expected to be wise in responding to opportunities and challenges in every changing era. An understanding of the history of the nation can strengthen a sense of nationalism or strengthen identity as a nation, so that students or young people have a strong personality or principle in facing the era of the industrial revolution 4.0. In fact, the History Education Study Program is still in demand, even though the enthusiasts are not as big as other study programs such as the PPKn study program or the Economic Education Study Program, there are several reasons that motivate entry to the History Study Program, among others: because they were motivated by history teachers when they were in schools before, but there are those who are genuinely interested because they understand the function of the History subject as a means of strengthening the national identity. The Industrial Revolution 4.0 is a challenge for prospective history teachers, because they must have technological competence to support history learning. Strong motivation and positive perceptions of the existence of the History Study Program can help graduates adapt to technology so that they have competence. Keywords: Historical Education, Industrial Revolution 4.0